The three-headed one at the crossroad - Dynda, Jiří (Studia mythologica Slavica, 2014)
This paper introduces a comparative analysis combined with a historical source overview concerning a particular Slavic god: Triglav. The aim of this paper is to verify the hypothesis that Triglav was, in the cosmological perspective, a deity connecting the structured layers of the world. Numerous indications from various written and archaeological sources may be drawn upon in the forming of a comprehensive picture of competences of this deity.
Keywords: mitologija; mythology; primerjalna mitologija; comparative mythology; Slavic mythology; Slavs; Slovani; božanstva; mitološka bitja